ABSTRACT Background: Hypertension is one of the non-communicable diseases that is still a health problem because it can cause heart disease, brain injury, vision and kidney disorders. The data of hypertensive patients in Puskesmas Pamitran in 2015 increa - Amalia, Icca Stella; ., Ismayati; Sobirin, Ahmad (Jurnal Ilmu Kesehatan Bhakti Husada: Health Sciences Journal, 2017)
Background: Hypertension is one of the non-communicable diseases that is still a health problem because it can cause heart disease, brain injury, vision and kidney disorders. The data of hypertensive patients in Puskesmas Pamitran in 2015 increased by 1,268 people. The wrong diet and lack of physical activity is one of the risks that the disease hypertension. Researchers will see whether there is a relationship between diet and physical activity on the level of hypertension at Pamitran Puskesmas 2017. The purpose of this study is to know the relationship between diet and physical activity with the level of hypertension in the work area Puskesmas Pamitran Year 2017. Method: The design of this research is qualitative analytic with cross sectional approach, it is done at puskesmas pamitran in August 2017. The research population is 66 people and the sample is 55 people with accidental method. Relationship analysis using chi-square test. Results: There was a significant relationship between diet and hypertension rate in hypertensive patients at Puskesmas Pamitran (? = 0,033). There was a correlation between physical activity and hypertension rate in hypertensive patients at Puskesmas Pamitran (? = 0.001).